Smear Layer Removal Efficacy of EDTA and Citric Acid in Endodontics - Atiquzzaman Khan; Rubaba Ahmed (Update Dental College, 2023)
Introduction: Smear layer is formed by organic and inorganic components generated during endodontic instrumentation. Smear layer has many deleterious effects on the success of root canal treatment. So removal of smear layer is advocated. Sodium Hypochlorite (NaOCl) and a chelating agent like Ethylene Diamine Tetra Acetic Acid (EDTA) or Citric Acid is commonly used alternatively to remove smear layer. But the alternate use increase dentine erosion in root canal surface. This in vitro study attempts to compare the smear layer removal efficacy of 15% EDTA & 10% Citric Acid as a final rinsing solution. Materials and Methods: Forty extracted, single rooted and single canal human anterior tooth were used. Endodontic preparation of the root canal was done after grouping and access cavity preparation. Final irrigation was given with 15% EDTA & 10% Citric Acid to the test groups and distilled water control groups and kept for one minute. Photomicrograph of the root canal surface at 3000X magnification at coronal, middle and apical regions were taken with the help of SEM and scoring for smear layer removal was done. Data was analyzed using SPSS version 16 and were compared with the control samples and subjected to statistical analysis by one way ANOVA and Bonferroni multiple comparison tests at 5% level of significance. Result: The test solutions removed smear layer but none could be removed completely from all of the three root canal regions. 10% Citric Acid removed smear layer better from the coronal and middle region but in apical region 15% EDTA produced a better result. The difference of smear layer removal efficacy of 15% EDTA & 10% Citric Acid with the Control solution was found statistically significant (p<0.001) but in between 15% EDTA & 10% Citric Acid it was not significant in all three root canal regions. Conclusion: Regarding the smear layer removal efficacy of 10% Citric Acid was found better as a final rinse solution. Update Dent. Coll. j: 2023; 13(2):9-14